Insights into maize starch degradation by sulfuric acid from molecular structure changes. (1st February 2020) - Li, Hongyan; Yan, Shu; Mao, Huijia; Ji, Jingyun; Xu, Minghao; Zhang, Shan; Wang, Jing; Liu, Yingli; Sun, Baoguo
Highlights: Sulfuric acid hydrolysis dramatically reduces the molecular size of starch. Acid hydrolysis gradually decreases amylose content from 28.3 % to 4.6 %. The starch CLD is significantly changed by acid hydrolysis, especially for amylose. The long chains might play a role in maintaining molecular size of amylopectin. Abstract: In this study, the molecular structure of hydrolyzed maize starch by sulfuric acid is analyzed by characterizing the chain-length distribution (CLD) and molecular size. It is found that molecular size is dramatically reduced by acid hydrolysis for only 1 h while amylose content is gradually decreased from 28.3 % to 4.6 % with hydrolysis time prolonging. By quantifying the subtraction of CLDs between hydrolyzed sample and native starch, we find: 1) the long chains with degree of polymerization (DP)∼500–30000 of native starch are degraded by acid hydrolysis for only 1 h; 2) with hydrolysis time extending, the degradation of short-amylose chains and even short amylopectin chains are initialized; 3) molecular size of hydrolyzed starch shows a strong correlation with the parameters derived from the subtraction analysis. This study could help to further understand molecular features from the individual chain assembling to a fully branched molecule.